RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND WORK MOTIVATION WITH PERFORMANCE IN EMPLOYEE AGENCY IN REGIONAL EMPLOYMENT IN JAKARTA - Novi Lanjar Sari (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
ABSTRACT The purpose of this study is to determine the correlation between culture organization and work motivation with the employee performance of Badan Kepegawaian Daerah in Jakarta. The research method used is survey method with the correlation approach, population used are all employee in Badan Kepegawaian Daerah DKI Jakarta. The sampling technique used technique of purposive sampling as many as 100 people. Based on the result of analysis and discussion, it is known that there is positive and significant correlation between culture organization and employee performance, there is positive and significant correlation between work motivation and employee performance, and also there is positive and significant correlation between culture organization and work motivation with employee performance of Badan Kepegawaian Daerah in Jakarta. Key word: Employee Performance, Culture Organization, Work Motivation